Design-guided intracavity-doubled Cr:LiCAF laser with optimized long-term robustness and 377–424 nm tunability - Erturk, Zekican; Okuyucu, Serdar; Ozturk, Yusuf; Demirbas, Umit (Applied physics. B, Lasers and optics)
Short, highly doped Cr:LiCAF crystals can exhibit very low passive loss and high efficiency but are prone to thermally induced internal damage. Here we instead use a 15 mm, low-ion-doped (1.25%) Cr:LiCAF crystal, accepting somewhat higher passive loss in exchange for improved thermal robustness and longer expected lifetime, and demonstrate its continuous-wave (CW) intracavity second-harmonic generation (SHG) into the violet. The Cr:LiCAF oscillator delivers 1.85 W of CW output at 790 nm with 5.8 W of absorbed pump power, corresponding to a 38% slope efficiency, and is continuously tunable from 747 nm to 870 nm using a 2-mm off-axis birefringent filter (BRF). Efficient SHG to the blue–violet is achieved by placing Type-I BBO/BiBO crystals at a secondary intracavity waist, yielding up to 440 mW of CW power near 400 nm (7.6% optical-to-optical efficiency) with 1.1% RMS stability over 10 min. By combining crystals optimized for fundamentals near 775, 800, and 825 nm and adjusting phase-matching, we achieve continuous SH tuning from 377 nm to 424 nm. The 400 nm SH beam exhibits walk-off-induced ellipticity with beam-quality factors of M 2 ≈ 12.2 (sagittal) and M 2 ≈ 1.9 (tangential), while the 800 nm fundamental shows M 2 ≈ 5.5 and 1.2, respectively. Beyond performance metrics, we provide a systematic analysis linking crystal length and focusing to conversion efficiency, offering practical guidelines for compact, broadly tunable violet sources based on intracavity-doubled Cr:LiCAF lasers.